2005
DOI: 10.3171/jns.2005.102.2.0290
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for intracranial meningiomas in the elderly: a clinical—radiological grading system as a predictor of outcome

Abstract: The CRGS score is a useful and practical tool for the selection of elderly patients affected by intracranial meningiomas as surgical candidates. A CRGS score higher than 10 and female sex are good prognostic factors of survival. whereas age is not a contraindication to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 10 publications
0
42
0
3
Order By: Relevance
“…Previous studies have reported that the 30 day postoperative mortality rate is 0-10.8% in elderly meningioma patients (10,15,17,38). A recent prospective study of surgical resection of intracranial meningiomas reported that elderly patients (>70 years) exhibited significantly higher 30-day postoperative mortality rates (12.0%) than younger patients (4.6%) (6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that the 30 day postoperative mortality rate is 0-10.8% in elderly meningioma patients (10,15,17,38). A recent prospective study of surgical resection of intracranial meningiomas reported that elderly patients (>70 years) exhibited significantly higher 30-day postoperative mortality rates (12.0%) than younger patients (4.6%) (6).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, age was not an independent factor for predicting surgical outcome (7,10,15); in the present study it was demonstrated that age was not associated with increased surgical risk in elderly patients with intracranial meningioma, which was consistent with previous studies (7,10,15). Several studies have assessed predictors for surgical outcome in elderly meningioma patients using CRGS, GSS and SKALE scoring systems that include tumor size, gender, KPS score, ASA score, tumor location, peritumoral edema and concomitant disease (9,10,16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations